Ameliorating the toxic effects of Acacia angustissima with polyethylene glycol in rats - Smith, A.H.; Wallig, M.A.; Seigler, D.S.; Odenyo, A.A.; McSweeney, C.S.; Mackie, R.I. (Elsevier, 2003)
*Acacia angustissima* is a tropical legume, which has potential as a fodder tree, but contains secondary compounds which have an anti-nutritional effect in ruminants. This study was designed to indicate whether condensed tannins alone are responsible for the anti-nutritional affect or whether non-protein amino acids or other unidentified plant components contribute to the anti-nutritional effect. Feeding rats diets containing ground plant material or purified *A. angustissima* polyphenolics at similar levels of polyethylene glycol (PEG) binding capacity (3.9 g/100 g dry matter (DM)) resulted in weight loss (-8.4 and -10.2 g per day) and reduced intake (3.4 and 2.9 g per day) in both groups compared to average daily gain (1.4 and 1.5 g per day) and intake (15.8 and 17.4 g per day) of control diets. The effect on intake and average daily gain was ameliorated by the addition of PEG, which complexes with phenolic compounds. These results verify that in rats the anti-nutritional effect is caused by polyphenolics in *A. angustissima*.